The Role of Libraries in Strengthening Information Literacy toward Filter Bubble and Echo Chamber in Algorithm-Based Digital Information Consumption - Astrid Ola Zuleika; Retno Sayekti (Jurnal IPTEK Bagi Masyarakat, 2026)
Digital technology has changed how people access information, especially through the internet, social media, and search engines. However, algorithmic personalization may limit information diversity and create filter bubbles and echo chambers. This study analyzes the role of libraries in raising public awareness of these phenomena in digital information consumption. Using a descriptive qualitative approach, the research was conducted at the Medan City Library and Archives Office with nine informants consisting of librarians and library users selected through purposive sampling. Data were collected through interviews, observation, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings show that users rely on digital media because it is fast and accessible, but this also increases the risk of homogeneous information exposure and weak information verification. Libraries support information literacy through credible sources, reference services, literacy programs, digital literacy seminars, digital library training, and anti-hoax education. This study concludes that libraries can help communities become more critical and selective in consuming algorithm-based digital information.